Pendampingan Teknis Pembuatan Kompos Berbahan Dasar Tumbuhan Tithonia Pada Kelompok Tani Guci Sehati Kanagarian Lasi Kabupaten Agam - Rizki, Rizki; Darmansyah; Rasdanelwati; Jonni; Yefriwati; Olivia Darlis; Sari Rukmana Okta Sagita Chan; Chairunnisak; Rovel Lando Fambari; Agung Ramadhano; Hawari; Yopa Dwi Mutia (Gayaku Publisher, 2025)
The Guci Sehati Farmer Group in Nagari Lasi faces several fundamental challenges in their agricultural practices, one of which is dependence on synthetic chemical fertilizers. These fertilizers lead to high production costs and trigger degradation of the soil's physical, chemical, and biological structure. The lack of knowledge about using nature-based materials is a challenge for implementing cultivation practices in this farmer group. Additionally, there is an abundance of locally available organic materials such as agricultural waste, weeds, and livestock manure that have not been optimally utilized for producing environmentally friendly fertilizers. This community service program focuses on technical mentoring for making Tithonia-based compost at the Guci Sehati Farmer Group, Kanagarian Lasi, Agam Regency. The main problems faced by partners are high dependency on synthetic chemical fertilizers, expensive agricultural inputs, and suboptimal utilization of local biomass such as Tithonia diversifolia which is abundant in the surrounding environment. The aim of this activity is to empower farmers with skills to make quality organic fertilizer to create more sustainable and independent agriculture. The implementation method includes three main stages: (1) socialization and direct demonstration of Tithonia composting techniques, (2) participatory assistance during the fermentation and turning process, and (3) monitoring and evaluation of compost quality. The mentoring results showed a significant increase in farmers' capacity, where all participants successfully produced Tithonia compost that met physical quality standards, namely dark brown color, crumbly texture, stable temperature, and no odor. The conclusion of this activity is that participatory technical assistance is effective in transferring Tithonia composting technology, reducing dependence on chemical fertilizers, and optimizing local resources, thus directly contributing to strengthening food sovereignty and implementing sustainable agriculture at the farmer level.